2005
DOI: 10.1079/9780851998145.0000
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative aspects of ruminant digestion and metabolism

Abstract: This book aims to bring together the quantitative approaches concerned with elucidating mechanisms used in the study of ruminant digestion, metabolism and related areas from different contributing practitioners, experts and scientists. A great deal of research had been carried out on the digestive system of ruminants and also led to studies on the peculiarities of metabolism that cope with unusual products of microbial digestion. Quantitative approaches to ruminant physiology and special features of the rumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(15 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Residual ash-free NDF of the fermented samples was obtained at 0,6,12,24,30,36,48,72,96,120,144,216, and 240 h based on the procedure of Mertens (2002). Observations were taken more often at earlier time points to offset the greater variation that occurs during the first part of the fermentation and digestion of the substrate (Mertens, 2005). We omitted the use of sodium sulfite for the NDF analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual ash-free NDF of the fermented samples was obtained at 0,6,12,24,30,36,48,72,96,120,144,216, and 240 h based on the procedure of Mertens (2002). Observations were taken more often at earlier time points to offset the greater variation that occurs during the first part of the fermentation and digestion of the substrate (Mertens, 2005). We omitted the use of sodium sulfite for the NDF analyses.…”
Section: Methodsmentioning
confidence: 99%
“…One of the problems in describing digestion kinetics is that residues remaining at any digestion time are a mixture of undigested and indigestible matter (Mertens, 2005). Furthermore, Mertens (1973Mertens ( , 1977 and Mertens and Ely (1979) indicated that overall digestion is better predicted assuming that the pdNDF fraction is the sum of 2 digestible fractions that can be described by 2 first-order functions but with different rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, hempseed oil has lower ruminal fermentation parameters compared to soybean and canola oil ( Table 6). Total volatile fatty acids (VFA) can be as high as 200 mM just after feeding or decrease as low as 30 mM, however, its normal range is 70-120 mM (112). Low total VFA (37 mM) from hempseed oil could be an indicator of depressed rumen formation.…”
Section: Nutrient Digestibilitymentioning
confidence: 99%
“…These compounds accumulate in cytoplasmic membranes as they are lipophilic thus disrupting methanogen cell membranes (118). Although methane production is important in maintaining ruminal environment redox balance by providing a pathway for the excess pyruvate (112), it decreases the amount of ME obtained from a diet (69), hence, increasing energy required for meat production. The decrease in the concentration of methane produced may reduce atmospheric greenhouse gases and increase feed utilization efficiency as its emissions represent about 10% of gross energy loss from feed intake (120).…”
Section: Nitrogen and Methane Emissionsmentioning
confidence: 99%
“…These short-chain fatty acid degradation pathways are formed from nondigestible carbohydrates in the gut microbiome in adults (37). In both humans and sheep, propanoate and butanoate metabolism lead to the production of acetyl-CoA for entry into the TCA cycle, whereas in sheep, propionate metabolism has been shown to stimulate gluconeogenesis (20). Succinate, present in both butanoate and propanoate metabolism, was more abundant in fetal cardiac tissue (Table 1).…”
Section: Discussionmentioning
confidence: 99%